2014
DOI: 10.6007/ijarbss/v4-i4/808
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effective Factors on Online Purchase Intention through Theory of Planned Behavior

Abstract: As the rapid growth of the World Wide Web, electronic commerce has become a new way for businesses on online markets. Du to its facilities, many people are willing to shop online. Although business-to-consumer e-commerce has created new businesses opportunities, questions about consumer shopping motivations toward online shopping versus conventional shopping continue to persist. The purpose of this study is to investigate factors which affect online purchase intention. In this regard, providing a conceptual fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Extant studies reveal that marital status, education, location of residence, gender, household income, and age were predictors of online buying [29]. The eagerness and preference of consumer in adopting the online channel was also positively linked to income, innovativeness and household size [30]. Studies shows that women represent the major online holiday season shoppers [28].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Extant studies reveal that marital status, education, location of residence, gender, household income, and age were predictors of online buying [29]. The eagerness and preference of consumer in adopting the online channel was also positively linked to income, innovativeness and household size [30]. Studies shows that women represent the major online holiday season shoppers [28].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Research conducted by Ketabi, Ranjbarian, and Ansari (2014) shows that subjective norms directly influence purchase intentions online. In line with the results of these studies, other studies about halal food, also found that subjective norms influence a person's purchase intention (Afendi, Azizan, & Darami, 2014).…”
Section: Effect Of Subjective Norms On Purchase Intentionmentioning
confidence: 99%
“…An empirical study from Yean et al (2015), Ham et al (2015), Anggelina and Japarianto (2014), Ketabi et al (2014), and Afendi et al (2014) explained that subjective norms influence someone's purchase intention, so the hypothesis can be drawn as follows:…”
Section: Effect Of Subjective Norms On Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of planned behavior has been used extensively in marketing research and is widely accepted as a model to predict purchase intentions in many contexts (e.g. online purchasing, organic food, real estate market) (Al-Nahdi et al, 2015;Arvola et al, 2008;George, 2004;Ketabi, Ranjbarian, & Ansari, 2014;Omar, Nazri, Osman, & Ahmad, 2016;Yazdanpanaha & Forouzania, 2015). However, to our knowledge the TPB has not been tested with the inclusion of familial relationship complexity when it comes to joint decisions.…”
Section: Introductionmentioning
confidence: 99%